Enhancing Teacher Performance Management in Islamic Schools: A Case Study in Madrasah Aliyah Minat Kesugihan Cilacap - Winarsih, Sri (STAI Hubbulwathan Duri, 2024)
Teacher performance management is essential to improving education quality, especially in Islamic schools like MA Minat Kesugihan Cilacap. This study examines the role of Musyawarah Guru Mata Pelajaran (MGMP), training, and certification in optimizing teacher performance management. Using a qualitative case study method, data were collected through interviews, observations, and documentation. Researchers observed classroom activities, MGMP meetings, and training sessions, and conducted in-depth interviews with teachers, the madrasah head, and administrative staff. Documents such as performance reports, MGMP notes, training materials, and teacher certificates were also analyzed. The findings reveal that an integrated management approach—comprising planning, organizing, implementing, and monitoring—enhances teaching quality, knowledge, skills, and professional attitudes. Consistent teacher certification programs significantly improved teacher professionalism and motivation. These results emphasize the importance of structured management in fostering teacher development and improving overall educational quality. The study concludes that optimizing teacher performance management through structured planning, training, MGMP involvement, and certification can serve as a model for other madrasahs aiming to improve teaching outcomes and educational quality.